PARTITION PERSPECTIVES OF KHUSHWANT SINGH BISHAM SAHANI AMRITA PRITAM AND ATTIA HOSSAIN - Anil Kumar singh (International Journal of Multidisciplinary Research and Studies, 2021)
In this context, "partition" refers to the process by which India and Pakistan each became their own independent nation. In 1947, British India was partitioned into the dominion nations of India and Pakistan through the process known as "partition." The partition of India was a terrible and despicable occurrence that irrevocably altered the relationship between Hindus and Muslims. This should not have had to happen, and it is the result of the policies of the British government as well as the intrigues of some Hindu and Muslim leaders. These events had played havoc with the lives of individuals from both countries, as well as with their properties. This occurrence not only has a substantial impact on the economic, psychological, social, political, cultural, or humanitarian elements of the sub-continent, but it also has an impact on the politics of the entire world. Despite the fact that partition is typically regarded as the simple and peaceful split of lands or territory, about one million people lost their lives during the partition of India and Pakistan. The merging of literature and culture, as well as art and tradition, is one of the beneficial results that this split has brought about. Before the partition, India was famous for the multiculturalism, multilingualism, and diversity that existed throughout its society. In August of 1947, it was disassembled into its component pieces. Violence, rioting, an unprecedented bloodbath, pools of blood, dead corpses, and unending, indelible anguish were all caused by Partition. These events will never be forgotten. On each side of the recently established boundary, there were significant numbers of refugees. It is also responsible for the proliferation of poverty, joblessness, and starvation.